ANALYZING THE IMPACT OF METAVERSE TECHNOLOGY ON SOCIAL DEVELOPMENT: A FIELD STUDY ON GENERATION Z IN INDIA - Banerjee, Debosmita; Roy, Koyel; Mahapatra, Sneha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the contemporary digital era, the emergence of the metaverse presents a transformative landscape, intertwining virtual experiences with real-world implications. This research embarks on an interdisciplinary exploration to unravel the multifaceted impact of the metaverse on the mental health of young, educated adults, with a special focus on the socio-legal dimensions shaping this digital frontier. Drawing upon established legal principles, socio-legal theories, and empirical evidence, this research delves into the social dynamics, identity construction, and overall mental well-being of individuals immersed in the metaverse. By synthesizing doctrinal analysis with empirical insights, the study seeks to uncover the nuanced interplay between virtual experiences and psychological well-being. Furthermore, this research endeavors to scrutinize the legal frameworks—or the absence there-of that govern the metaverse, considering the implications for user rights, privacy, and governance. Through a meticulous examination of existing legal precedents, legislative frameworks, and emerging challenges, the study aims to shed light on the regulatory landscape of this digital realm.The central inquiry of this research revolves around understanding how engagement with the metaverse influences the mental health trajectories of young, educated adults. By posing critical questions and offering doctrinal insights, the research endeavors to contribute to both theoretical discourse and practical implications for policymakers, legal practitioners, and mental health professionals alike.